Diagnostic Performance of Magnetic Resonance Imaging for Preoperative Local Staging of Penile Cancer: A Systematic Review and Meta-Analysis - Rocco Simone Flammia; Antonio Tufano; Luca Antonelli; Arianna Bernardotto; Alberto A. Castro Bigalli; Zhen Tian; Marc C. Smaldone; Pierre I. Karakiewicz; Valeria Panebianco; Costantino Leonardo (Applied Sciences, 2021)
Invasion of the tunica albuginea (TA) and/or urethra are key factors in determining the feasibility of organ-preserving surgery in penile cancer (PC). Magnetic resonance imaging (MRI) appeared to be a promising technique for preoperative local staging. We performed a systematic review (SR) and pooled meta-analysis to investigate the diagnostic performance of MRI in preoperative local staging of primary PC. An SR up to May 2021 was performed according to the PRISMA statement. The diagnostic performance of MRI was evaluated according to TA invasion, urethra invasion, and pT-stage ≥ 2. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) from eligible studies were pooled and summary receiver operating characteristic (SROC) curves were constructed. Overall, seven qualified studies were deemed suitable. Diagnostic performance of MRI showed an accuracy of 0.89 for TA invasion (sensitivity 0.78, PPV 0.79, specificity 0.91, and NPV 0.90); an accuracy of 0.88 for urethra invasion (sensitivity 0.65, PPV 0.46, specificity 0.86, and NPV 0.93); an accuracy of 0.90 for pT ≥ 2 (sensitivity 0.86, PPV 0.84, specificity 0.70, and NPV 0.73).Currently available evidence indicates that MRI might be a one-stop shop for local staging of primary PC and play a central role with regard to conservative surgical management.